2017
DOI: 10.4236/jwarp.2017.97051
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bioassessment Tools for Ecological Status Using Macrozoobenthic Community in Upstream Area (Case Study: Citarum River, West Java, Indonesia)

Abstract: This research aims to develop an assessment tool of ecological status in the upstream area using macrozoobenthic community and its relationship to the physicochemical parameters of water and sediment, in Citarum River. The number of species and abundance of macrozoobenthos in the dry season was higher compared to rainy season. The predominant family (Pachychilidae, Hydropsychidae, Glossiphonidae, and Chironomidae) obtained in both season was significantly correlated with the physicochemical parameter. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…The matrix contains the range of values for each physicochemical parameter and the abundance of predominant macrozoobenthos which determine the ecological status. The determination of the concentration range of physicochemical parameters is based partly on literature studies such as total sediment nitrogen and percent of gravel [7]; TSS [7,16,17]; conductivity [16,17]; and NO3, NO2, BOD, NH3 [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The matrix contains the range of values for each physicochemical parameter and the abundance of predominant macrozoobenthos which determine the ecological status. The determination of the concentration range of physicochemical parameters is based partly on literature studies such as total sediment nitrogen and percent of gravel [7]; TSS [7,16,17]; conductivity [16,17]; and NO3, NO2, BOD, NH3 [17].…”
Section: Discussionmentioning
confidence: 99%
“…The ecological status of the upstream area of Citarum River basin was determined by a scoring system developed by Chazanah et al [7] as shown in Table 2 and calculated according to Eq. (1).…”
Section: Ecological Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Makroinvertebrata dapat digunakan untuk memantau kualitas air berdasarkan faktor biologis. Apabila dibandingkan dengan indikator fisika dan kimia, makroinvertebrata menjadi salah satu pilihan sebagai bioindikator yang akurat dan dapat mengintegrasikan kualitas dari suatu perairan (Chazanah et al, 2017). Makroinvertebrata memiliki kisaran toleransi yang berbeda-beda terhadap lingkungan dan sangat peka terhadap perubahan kualitas air di habitatnya sehingga akan berpengaruh terhadap komposisi dan kelimpahan pada komunitasnya (Hendrasarie, 2019).…”
Section: Pendahuluanunclassified